Borderline intellectual functioning: an increased risk of severe psychiatric problems and inability to work. - Peltopuro, M.; Vesala, H. T.; Ahonen, T.; Närhi, V. M. (Journal of Intellectual Disability Research, 2020)
Background: The use of facilities such as disability pension, psychiatric care, health care and services for people with intellectual disabilities and borderline intellectual functioning (BIF) were compared with the general population and two other study groups comprising people with mild intellectual disabilities (MIDs) and learning problems (LPs). Methods: The population‐based sample (N = 416,973), 'Finland‐in‐Miniature', was gathered in 1962 and followed until 1998. For the purpose of the present study, three groups were formed: BIF (n = 416), MID (n = 312) and LP (n = 284). The use of services was examined with the help of national registers. Results: As compared with the general population, people with BIF had been granted disability pension 2.7 times more often and had been patients in psychiatric care 3.4 times more often. They had also systematically used more services than people with LP. Conclusions: People with BIF are at risk of inability to work and facing severe mental health problems. They also seem to have more severe psychiatric problems than people with MID and LP. There is, therefore, a crucial need for increasing the awareness in society of BIF. Although this study's follow‐up data were collected about 20 years ago, it is still relevant because people with BIF are a neglected group and still face growing demands in school and work life with no marked changes in services.